Vaccarin suppresses diabetic nephropathy through <?A3B2 pi6?>inhibiting the EGFR/ERK1/2 signaling pathway - Zhu Xuexue; Meng Xinyu; Du Xinyao; Zhao Chenyang; Ma Xinyu; Wen Yuanyuan; Zhang Shijie; Hou Bao; Cai Weiwei; Du Bin; Han Zhijun; Xu Fei; et al. (Acta Biochimica et Biophysica Sinica)
<?A3B2 tlsb=.005w?>Diabetic nephropathy (DN) is recognized as one of the primary causes of chronic kidney disease and end-stage renal disease. Vaccarin (VAC) confers favorable effects on cardiovascular and metabolic diseases, including type 2 diabetes mellitus (T2DM). Nonetheless, the potential role and mechanism of VAC in the etiology of DN have yet to be completely elucidated. In this study, a classical mouse model of T2DM is experimentally induced via a high-fat diet (HFD)/streptozocin (STZ) regimen. Renal histological changes are assessed via H&E staining. Masson staining and immunohistochemistry (IHC) are employed to assess renal fibrosis. RT-PCR is utilized to quantify the mRNA levels of renal fibrosis, oxidative stress and inflammation markers. The levels of malondialdehyde (MDA) and reactive oxygen species (ROS), as well as the content of glutathione peroxidase (GSH-Px), are measured. The protein expressions of collagen I, TGF-β1, α-SMA, E-cadherin, Nrf2, catalase, SOD3, SOD2, SOD1, p-ERK, p-EGFR (Y845), p-EGFR (Y1173), p-NFκB P65, t-ERK, t-EGFR and t-NFκB P65 are detected by western blot analysis. Our results reveal that VAC has a beneficial effect on DN mice by improving renal function and mitigating histological damage. This is achieved through its inhibition of renal fibrosis, inflammatory cytokine overproduction, and ROS generation. Moreover, VAC treatment effectively suppresses the process of epithelial-mesenchymal transition (EMT), a crucial characteristic of renal fibrosis, in high glucose (HG)-induced HK-2 cells. Network pharmacology analysis and molecular docking identify epidermal growth factor receptor (EGFR) as a potential target for VAC. Amino acid site mutations reveal that Lys-879, Ile-918, and Ala-920 of EGFR may mediate the direct binding of VAC to EGFR. In support of these findings, VAC reduces the phosphorylation levels of both EGFR and its downstream mediator, extracellular signal-regulated kinase 1/2 (ERK1/2), in diabetic kidneys and HG-treated HK-2 cells. Notably, blocking either EGFR or ERK1/2 yields renal benefits similar to those observed with VAC treatment. Therefore, this study reveals that VAC attenuates renal damage via inactivation of the EGFR/ERK1/2 signaling axis in T2DM patients. <?A3B2 tlsb?> <?Pub Caret 40?>